The atmospheric monitoring system of the JEM-EUSO instrument - Adams, J. H. (2015)
The JEM-EUSO telescope will observe Ultra-High Energy Cosmic Rays (UHECRs) from space, detecting the UV Fluorescence Light produced by Extensive Air Showers (EAS) induced by the interaction of the cosmic rays with the earth?s atmosphere. The capability to reconstruct the properties of the primary cosmic ray depends on the accurate measurement of the atmospheric conditions in the region of EAS development. The Atmospheric Monitoring (AM) system of JEM-EUSO will host a LIDAR, operating in the UV band, and an Infrared camera to monitor the cloud cover in the JEM-EUSO Field of View, in order to be sensitive to clouds with an optical depth tau >= 0.15 and to measure the cloud top altitude with an accuracy of500 m and an altitude resolution of 500 m.